AN ANALYSIS OF CHARACTER EDUCATION VALUES IN THE ELT TEXTBOOK FOR JUNIOR HIGH SCHOOL STUDENTS - Prastika Sukma, Azura Dwi; Suharjito, Bambang; Fitriani, Ika (ELLTER Journal, 2025)
Character education (CE) is essential in developing students' personalities. In character development, English Language Teaching (ELT) textbooks have a vital role in supporting character education. However, ELT textbooks published in Indonesia and abroad underrepresent the characters that fulfill the curriculum goals of CE. Based on previous research that had been conducted in Indonesia, English textbooks in the 2013 curriculum were not representative of Indonesian culture and showed character gaps in the textbooks. Therefore, this research investigated CE in the English textbook based on the emancipated curriculum. This study analyzed the ELT textbook for the seventh-grade junior high school in the current curriculum called “English for Nusantara” by utilizing the Pancasila Student Profile to analyze CE. Content analysis by Ary et al. (2010) was selected as an analysis method for analyzing CE through visual materials. The results show that there are character gaps presented in ELT textbooks. The characters of having Faith fear of the Almighty God and noble character are more dominant in the textbook. This provides an opportunity for future researchers to examine CE by investigating diverse research objects so that CE can be conveyed relevantly.